Unilateral Uterine Torsion in a Shorthair Scottish Queen - Rişvanlı, Ali; Taş, Abuzer; Kyzy, Aiperi Aitmyrza; Uulu, Nur Abdımanap; Kyzy, Sezim Belek; Duysobayeva, Aiturgan (Kyrgyz-Turkish Manas University, 2022)
In this case report, it is aimed to present unilateral uterine torsion in a 7-year-old Shorthair Scottish queen. The queen, which had full-term pregnancy, was brought to the Kyrgyz-Turkish Manas University Veterinary Faculty Teaching hospital with complaints of stagnation, vomiting and hypothermia. In the ultrasonography examination, 3 kittens without a heartbeat were detected. After the abdominal incision made in the queen for whom emergency cesarean section was decided, a 1080o counterclockwise torsion was noticed on the caudal side of the cervix uterine in the left uterine horn of the queen. It was observed that the left uterine horn was cyanotic due to torsion-related ischemia. For this reason, it was decided to perform N-block ovariohysterectomy instead of cesarean section. As a result, it was concluded that the presented case report of unilateral uterine torsion, which is rare in cats, will make useful contributions to veterinarians and students in the field.
Keywords: Veterinary Surgery; Veteriner Cerrahi